Pengaruh Kompetensi Pedagogik, Motivasi dan Lingkungan Kerja Dalam Mempengaruhi Kinerja Guru di SMPN 27 Kota Bekasi - Sumarsih, Yayuk; Mulyanto, Heru (Syntax Literate, 2023)
Education is a very strategic vehicle in improving the quality of human resources which is a determinant factor of development. In this case the teacher is not merely a teacher who transfers knowledge, but also as an educator who transfers knowledge, but also as an educator who transfers values ​​as well as a mentor who provides direction and guides students in learning. Factors that affect the performance of a teacher can come from within the individual itself and factors from outside the individual. One of them is pedagogic competence, motivation, and work environment. The purpose of this study was to determine the simultaneous effect of pedagogic abilities, motivation and work environment on teacher performance at SMPN 27 Bekasi City and to determine the partial effect between pedagogic competence, motivation and the work environment of teachers at SMPN 27 Bekasi City. This research was conducted at SMPN 27 Bekasi City. The research was conducted from February 2022 to May 2022. The variables studied were pedagogic competence, motivation and work environment. The instruments used as a means of collecting research data are library studies and field studies. The method used in this study is quantitative, namely research based on data in the form of numbers that are processed by statistical analysis to influence between variables and the sample used is 53 samples. Instrument testing with validation and reliability tests. Data analysis using SPSS software with four stages. First, testing data quality. The second stage, the classical assumption test, the third stage performs multiple regression analysis. And the fourth is to test the hypothesis. The results showed that simultaneously, pedagogic competence (X1), motivation (X2), and work environment (X3) had a positive and significant effect on teacher performance. Partially it is proven that there is an effect of pedagogic competence on teacher performance. Partially it is proven that there is an influence of motivation on teacher performance. Partially it is proven that there is an influence of the work environment on teacher performance.